Preliminary Study On Potential Antimicrobial Activity Of Honey From Egricayir Plateau, Turkey - Tokbas Habip; Turhan Mahir (Journal of Apicultural Science, 2024)
Egricayir honey named after the Egricayir Plateau in Mersin, Turkey is rare and is said to have a healing effect by the local people. This preliminary and first-ever study on honey from the Plateau aims to investigate the claim through total antimicrobial activity (TA). Thirty honey samples were collected twice from the Plateau in early July and late August 2023, and then TA was determined through the use of the phenol equivalence test. Samples had a homogeneous TA distribution and each had a TA>10, lower limit for therapeutic potency. Of the samples, 28% had a therapeutically beneficial potency (10≤TA<20) and 72% had a therapeutically high potency (TA≥20). On average, the TA of the honey samples was 21 falling into the category of therapeutically high potency. The findings imply that the honey from the Egricayır Plateou is a good candidate for further therapeutic tests and geographical indication.